Assessment of the Effectiveness of the Dispute Adjudication Board: A Case Study of the Jakarta MRT Phase-1 - Dewi Sulistyaningsih (Journal of Social Research, 2026)
Construction dispute resolution is a major challenge in large-scale infrastructure projects, especially in complex and high risk Design and Build contract systems. Before the implementation of the Dispute Adjudication Board (DAB), projects with traditional contracts in Indonesia showed high Variation Order values, around 15–20% of the total contract, as well as relatively long dispute resolution duration. Jakarta MRT Phase 1 was the first project in Indonesia to implement DAB based on the FIDIC Yellow Book, while also applying the fast dispute resolution mechanism in Indonesia through binding decision. This study aims to assess the effectiveness of the DAB in improving efficiency of construction dispute resolution through a case study of Jakarta MRT Phase 1. This study uses qualitative descriptive method through literature review combined with case analysis of civil work packages CP101–CP106. It was found that DAB was able to resolve 11 disputes without escalation to arbitration and several were resolved through amicable settlement negotiations, with a low average variation order of 7.6% of the total initial contract price. These results indicate increase in time efficiency and legal certainty, although there are still challenges in terms of national regulations and human resource capacity in dispute management field.